SAR405838: A novel and potent inhibitor of the MDM2:p53 axis for the treatment of dedifferentiated liposarcoma - Bill, Kate Lynn J. (Clin Cancer Res, 2015)
PURPOSE: Dedifferentiated liposarcoma (DDLPS) is an aggressive malignancy that can recur locally or disseminate even after multidisciplinary care. Genetically amplified and expressed MDM2, often referred to as a “hallmark” of DDLPS, mostly sustains a wild-type p53 genotype, substantiating the p53-MDM2 axis as a potential therapeutic target for DDLPS. Here we report on the preclinical effects of SAR405838, a novel and highly selective MDM2 small-molecule inhibitor, in both in vitro and in vivo DDLPS models. EXPERIMENTAL DESIGN: The therapeutic effectiveness of SAR405838 was compared to the known MDM2 antagonists Nutlin-3a and MI-219. The effects of MDM2 inhibition were assessed in both in vitro and in vivo. In vitro and in vivo microarray analyses were performed to assess differentially expressed genes induced by SAR405838, as well as the pathways that these modulated genes enriched. RESULTS: SAR405838 effectively stabilized p53 and activated the p53 pathway, resulting in abrogated cellular proliferation, cell cycle arrest, and apoptosis. Similar results were observed with Nutlin-3a and MI-219; however, significantly higher concentrations were required. In vitro effectiveness of SAR405838 activity was recapitulated in DDLPS xenograft models where significant decreases in tumorigenicity were observed. Microarray analyses revealed genes enriching the p53 signaling pathway as well as genomic stability and DNA damage following SAR405838 treatment. CONCLUSION: SAR405838 is currently in early phase clinical trials for a number of malignancies, including sarcoma, and our in vitro and in vivo results support its use as a potential therapeutic strategy for the treatment of DDLPS.